TOOLNURSE: UMA FERRAMENTA WEB PARA CONSULTA DE ENFERMAGEM DE PUERICULTURA - Simas, Laura Taís Loureiro (2023)
The purpose of nursing consultations for children is to provide comprehensive, resolute and quality care. The nurse is able to identify needs, everyday situations, and is able to provide guidance according to the reality of families. The research is part of the Sustainable Development Goals, more specifically Goal 3: “Ensure a healthy life and promote well-being for all, at all ages”, as well as the Ministry of Health's Research Priorities Agenda, Axis 4 “Development of Technologies and Innovation in Health” and Axis 14 “Maternal and Child Health” and in the goals established by the Digital Health Strategy for Brazil 2020-2028. It is also consistent with the Project “Systematization of assistance and technological innovation in Nursing”, Thematic Area “Technology and Innovation in Nursing”, covered by the CAPES/COFEN Agreement Notice 08/2021. Objectives: To understand how the Family Health Strategy nurse develops the childcare nursing consultation; Build a tool with an emphasis on the physical examination of children under two years of age; Identify in the literature what should be included in the physical examination of children under two years of age; Develop a virtual tool as a resource for childcare nursing consultations. Methodology: The study included semi-structured interviews carried out with 15 nurses from the Family Health Strategy of Santa Maria-RS. Along with the analysis of the participants' statements, medical records and spreadsheets from nurses' care provided during childcare were observed. A tool was created with the collaboration of the areas of biomedical engineering, IT and design. Results: The designed device was a web application, entitled “Tool Nurse”, which will be used by nurses when caring for children and will be applied particularly in the physical examination, aimed at the age group of children under 2 years old. Final considerations: The study showed, like others before it, that nurses carry out several tasks and are currently especially involved in welcoming, which should be the responsibility of the entire team. Welcoming is another of the actions, but today it takes up a significant portion of their precious time. This time will be needed to develop preventive and promotional actions, as well as nursing consultations. For this, we need time and organization. It is the nursing consultations that show us the community, which consolidate the practice of care. The study showed weaknesses in nurses' care, however, the potential of their way of acting towards the population is something worthy of publicity in the media. It is imperative to say that such a device used by nurses will help children, as based on a quality physical examination it will be possible to detect problems and carry out interventions. These interventions could contribute to the mental health of small beings in the future. The product and its applicability: The “Tool Nurse” web application has potential and attributes that can collaborate with childcare nursing consultations, as such a tool can speed up, qualify and support the work process. Positively impacting communication with other team members, contributing to ongoing education and perhaps creating a database for future studies and health planning.